An Eco‐friendly Synthesis of Some Novel 4‐methyl‐4‐hetaryl Chromene and Pyrano[2, 3‐c]pyrazole Derivatives. (7th March 2017) - Abdelrazek, Fathy M.; Metz, Peter; Jäger, Anne; Metwally, Nadia H.
Abstract : Some novel chromene and pyrano[2, 3‐ c ]pyrazole derivatives could be achieved successfully by reacting cyclic β‐diketones with 2‐acetylfuran/2‐acetylthiophene and malononitrile in a one‐pot synthesis. Active methylene pyrazolones reacted with 2‐(1‐furan‐2‐yl‐ethylidene)‐malononitrile and 2‐(1‐thiophen‐2‐yl‐ethylidene)‐malononitrile derivatives to afford the desired pyrano[2, 3‐ c ]pyrazole derivatives. Structures of all new compounds were established based on analytical and spectral data as well as X‐ray crystallography. A plausible mechanism for the reaction is suggested. The solvents and catalyst used are environmentally benign, and no hazardous solvents or heavy metals were involved. Abstract :